SIMULASI KETERSEDIAAN BERAS DI JAWA TIMUR - Annisa Kesy Garside; Hasyim Yusuf Asjari (Jurnal Ilmiah Teknik Industri, 2015)
East Java province is one of the rice granary and is an important national food buffer. In 2014, East Java targeted to contribute 60% of 10 million tons national surplus in P2NB program. Objective of this research is to predict rice availability in 2013 to 2020 and analyze East Java readiness on achieving the target. Research steps starts from cause-effect diagram, stock and flow diagram, math formulation inside the diagram, verification and validation of the model, and simulation of developed model. Result of dynamical system indicates availability of rice in 2014 is 3,944,377.7 tons. With such availability, East Java target to contribute 60% of 10 million national rice surplus in 2014 cannot be achieved.